How robust are the STRONGER and STIL-STRONGER studies?. (January 2023) - Blobner, Manfred; Hunter, Jennifer M.; Ulm, Kurt
Summary: In 2020, the Sugammadex vs Neostigmine for Reversal of Neuromuscular Blockade and Postoperative Pulmonary Complications (STRONGER) study provided evidence for the first time that use of sugammadex is associated with fewer postoperative pulmonary complications than use of neostigmine. In a recent publication in the British Journal of Anaesthesia, a secondary analysis of the same data, the Association Between Neuromuscular Blockade Reversal Agent Choice and Postoperative Pulmonary Complications (STIL-STRONGER) study, has produced similar evidence of the advantages of sugammadex over neostigmine in high-risk and older patients undergoing prolonged, elective surgery. Here we consider the implications of the detailed statistical analysis used in these two studies and how its limitations could possibly have enhanced the statistical differences between the two drugs with respect to postoperative pulmonary complications.